2022
DOI: 10.3389/fphar.2022.927611
|View full text |Cite
|
Sign up to set email alerts
|

Puerarin: A protective drug against ischemia-reperfusion injury

Abstract: Ischemia-reperfusion (I/R) is a pathological process that occurs in numerous organs throughout the human body and is frequently associated with severe cellular damage and death. Puerarin is an isoflavone compound extracted from the root of Pueraria lobata and has pharmacological effects such as dilating cerebral vessels and anti-free radical generation in cerebral ischemic tissues. With the deepening of experimental research and clinical research on puerarin, it has been found that puerarin has a protective ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…The spinal cord is more susceptible to damage caused by ischemia due to poor segmental blood supply [ 2 ]. Studies have shown that the main mechanisms in spinal cord injury following ischemia-reperfusion are the occurrence of oxidative stress, excessive inflammation, and as a result, apoptosis of cells in the ischemia site [ 1 ]. Finally, all these cases can disrupt the function of the spinal cord and cause serious disturbance in nerve exchanges in the damaged spinal cord segments as well as the lower segments of the injured area.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The spinal cord is more susceptible to damage caused by ischemia due to poor segmental blood supply [ 2 ]. Studies have shown that the main mechanisms in spinal cord injury following ischemia-reperfusion are the occurrence of oxidative stress, excessive inflammation, and as a result, apoptosis of cells in the ischemia site [ 1 ]. Finally, all these cases can disrupt the function of the spinal cord and cause serious disturbance in nerve exchanges in the damaged spinal cord segments as well as the lower segments of the injured area.…”
Section: Discussionmentioning
confidence: 99%
“…Paraplegia caused by spinal ischemia-reperfusion injury (IR) during abdominal aortic surgery is one of the most terrible and catastrophic events [ 1 ]. The incidence of this destructive complication in patients undergoing surgery is estimated at 30% [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Puerarin is one of the main monomers of total flavonoids from Pueraria lobata, and is an isoflavone phytoestrogen with important pharmacological effects, minimal adverse reactions, and high safety [ 205 , 206 ]. It has been reported that puerarin exhibits various pharmacological activities, including anti-inflammatory, anti-oxidative stress, anti-apoptosis, and anti-autophagy effects, which are beneficial for alleviating myocardial ischemia/reperfusion injury and treating ischemic cardiovascular diseases [ 207 , 208 ]. Jiang et al found that puerarin could inhibit sorafenib-induced myocardial ferroptosis, and has a good protective effect against the cardiotoxicity of sorafenib.…”
Section: Molecular Mechanism Of Natural Products Regulating Ferroptos...mentioning
confidence: 99%
“…Puerarin is a flavonoid glycoside isolated from the root of the TCM Puerariae Lobatae Radix. Many researchers found that puerarin has a protective effect on ischemia-reperfusion injury of the heart, brain, spinal cord, lung, intestine, and other organs ( Gao et al, 2022 ). Studies have shown that puerarin may reduce the water channel function of AQP4 by regulating the cAMP/PKA/AQP4 pathway, thereby reducing subarachnoid hydrops ( Ying and Liu, 2020 ).…”
Section: Aqp Regulation By Tcms and Their Componentsmentioning
confidence: 99%